2009
DOI: 10.1007/s00454-009-9161-7
|View full text |Cite
|
Sign up to set email alerts
|

Uneven Splitting of Ham Sandwiches

Abstract: Let m_1,...,m_n be continuous probability measures on R^n and a_1,...,a_n in [0,1]. When does there exist an oriented hyperplane H such that the positive half-space H^+ has m_i(H^+)=a_i for all i in [n]? It is well known that such a hyperplane does not exist in general. The famous ham sandwich theorem states that if a_i=1/2 for all i, then such a hyperplane always exists. In this paper we give sufficient criteria for the existence of H for general a_i in [0,1]. Let f_1,...,f_n:S^{n-1}->R^n denote auxiliary f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…, S d+1 , there exists a unique hyperplane H which contains a given number of points from each set in its negative closed half-space. This discrete result builds upon previous continuous variants [1,4]. We first define a condition they require, which also plays a key role in our result.…”
Section: Generalized Resistant Hyperplane Mechanisms In High Dimensionsmentioning
confidence: 79%
See 2 more Smart Citations
“…, S d+1 , there exists a unique hyperplane H which contains a given number of points from each set in its negative closed half-space. This discrete result builds upon previous continuous variants [1,4]. We first define a condition they require, which also plays a key role in our result.…”
Section: Generalized Resistant Hyperplane Mechanisms In High Dimensionsmentioning
confidence: 79%
“…Definition 7 (Well Separable Sets [26] Well separable sets are sometimes called affinely independent sets [4]. Well separability is equivalent to various other conditions [4,37]. In what follows, Conv(·) denotes the convex hull.…”
Section: Generalized Resistant Hyperplane Mechanisms In High Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the case of five measures on R 3 , our approach from the proof of the hamburger theorem fails for the following reason. If µ i (R 3 ) = 1/5 for each i ∈ [5], then the target polytope, now in R 5 , intersected with the boundary of the box B, does not contain a closed curve symmetric with respect to the center of B. If such a curve existed, we could apply a generalization of the Borsuk-Ulam theorem saying that if f : S k → S k+l and g : S l → S k+l are antipodal maps, then their images intersect [14, Exercise 3.…”
Section: Discussionmentioning
confidence: 99%
“…For these more general measures, the condition µ i (H) = µ i (R d )/2 must be replaced by the inequality µ i (H) ≤ µ i (R d )/2. Breuer [5] gave sufficient conditions for the existence of more general splitting ratios. In particular, he showed that for absolutely continuous measures whose supports can be separated by hyperplanes, there is a hyperplane splitting the measures in any prescribed ratio.…”
Section: Simultaneous Partitions Of Measuresmentioning
confidence: 99%